Uneven Ground: Exploring the Impact of Geographical Region and Gender on Orthopaedic Surgery Resident Research Productivity - Natasja Lessiohadi, BA; Hayden Hartman, BS; James Pai, MS; William B. Goodman, BS; Mia V. Rumps, MS; Mary K. Mulcahey, MD (JBJS Open Access)
Introduction:. Research plays a crucial role in orthopaedic surgery advancement, patient outcomes, and both residency and fellowship training. This study aimed to examine associations between research productivity of orthopaedic surgery residents, gender proportion of residents, and the geographical region of orthopaedic surgery residency programs. Methods:. Using the Fellowship and Residency Electronic Interactive Database (FRIEDA) and the Doximity Residency Navigator, a list of the top 10 Accreditation Council for Graduate Medical Education (ACGME) orthopaedic surgery residency programs for each region (Northeast, South, Midwest, and West) were identified. FRIEDA, program websites, SCOPUS, PubMed, and ResearchGate were utilized to collect the following: residency program name, type, and location; and resident name, gender, H-index, and number of publications. Results:. Forty orthopaedic surgery residency programs and 1,377 residents across 4 regions were evaluated. Of these, 29.6% (408/1,377) were female and 70.4% (969/1,377) were male. Northeast programs averaged the highest publications (11.6) per resident, while the South averaged the fewest publications (5.9, p < 0.0001). Similarly, residents in Northeast programs had the highest average H-index (2.9), and residents in the South had the lowest average H-index (1.6) (f-ratio = 11.19, p < 0.0001). Male residents averaged more publications (9.0 vs. 5.5, p < 0.05) and higher H-indices (2.3 vs. 1.8, p < 0.05) than female residents. These differences were greatest in the South (male:female publication ratio = 1.9, H-index ratio = 1.4) and lowest in the Midwest (male:female publication ratio = 1.3, H-index ratio = 1.1). Conclusion:. At the top 10 orthopaedic surgery residency programs across all regions, female residents remain underrepresented in academic research compared with male residents, evidenced by a lower average number of publications H-indices, with the degrees of these discrepancies varying regionally. Further research is needed to identify the underlying factors influencing these differences. Program directors and orthopaedic surgery residents should be aware of these geographic and gender-based trends to improve their academic productivity and address the existing inequities within academic orthopaedics. Level of Evidence:. Level IV. See Instructions for Authors for a complete description of levels of evidence.